2019
DOI: 10.1210/en.2019-00321
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Regulation of Epimorphic Regeneration

Abstract: Studies aiming to uncover primary mechanisms of regeneration have predominantly focused on genetic pathways regulating specific stages in the regeneration process: wound healing, blastema formation, and pattern formation. However, studies across organisms show that environmental conditions and the physiological state of the animal can affect the rate or quality of regeneration, and endocrine signals are likely the mediators of these effects. Endocrine signals acting directly on receptors expressed in the tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 151 publications
0
11
0
Order By: Relevance
“…The most parsimonious explanation for these findings could be that, at least in the context of repeated amputations, there are as yet unidentified systemic components regulating mammalian digit tip regeneration. While local effectors of epimorphic regeneration have been the primary focus in the last decades, both cellular and humoral systemic mediators of epimorphic regeneration have been explored [ 43 , 44 ]. With the exception of deer antler regeneration [ 45 ], no such studies exist for mammalian epimorphic regeneration until now.…”
Section: Discussionmentioning
confidence: 99%
“…The most parsimonious explanation for these findings could be that, at least in the context of repeated amputations, there are as yet unidentified systemic components regulating mammalian digit tip regeneration. While local effectors of epimorphic regeneration have been the primary focus in the last decades, both cellular and humoral systemic mediators of epimorphic regeneration have been explored [ 43 , 44 ]. With the exception of deer antler regeneration [ 45 ], no such studies exist for mammalian epimorphic regeneration until now.…”
Section: Discussionmentioning
confidence: 99%
“…In vertebrates, the main signaling factors involved in blastema were Wnts, fibroblast growth factor 8 (FGF8), and FGF10, similar to the signaling factors involved in the growth of the regenerative limbs of larval Xenopus laevis (Yokoyama et al, 2011). Wnt activated FGF8, which in turn activated FGF10, forming a positive feedback pathway during AEC formation that promotes cell proliferation and the reconstruction of limb morphology (Easterling et al, 2019). A distal to proximal gradient of Wnt proteins was not detected using immunolabeling in S. tsinlingensis and P. muralis (Hutchins et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies find that age coincides with slower or faster regeneration (60-62) but also find other secondary factors (e.g., nutrition, seasonal variation, or stress) are associated with slower regeneration (63,64). A small study in Acomys found that older Acomys (≥3 years) regenerated 2mm biopsy punches to the ears slower than younger Acomys (2months) (65).…”
Section: Phenotypic Diversity In Ear-hole Closurementioning
confidence: 99%